2012
DOI: 10.1007/s00284-012-0235-z
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Tissue Influences on Endophytic Fungal Communities of Taxus chinensis var. mairei in China

Abstract: Endophytc fungi were collected from the barks, branches and leaves of Taxus chinensis var. mairei from the Jiangxi, Zhejiang and Chongqing regions of China and their influences on geographic and tissue investigated. A total of 145 fungal taxa were identified based on molecular techniques, of these 125 taxa (86.2 %) belonging to Ascomycota, 14 (9.7 %) to Basidiomycota, 5 (3.4 %) to Zygomycota, and 1 (0.7 %) to undefined fungi. The species richness and diversity of endophytic fungi were significantly affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…These differences could influence the EF diversity of those plantations. Some studies have reported that Shannon's diversity index of EF increases when the longitude decreases [80]; this finding is consistent with our results for Huatusco and Coatepec. In the other hand, in Veracruz, there is also a higher diversity of other organisms, such as small- and medium-sized mammals [81] in the rustic Huatusco plantations than in the simple polycultures of Huatusco, and in the different agroforestry systems of Coatepec.…”
Section: Discussionsupporting
confidence: 93%
“…These differences could influence the EF diversity of those plantations. Some studies have reported that Shannon's diversity index of EF increases when the longitude decreases [80]; this finding is consistent with our results for Huatusco and Coatepec. In the other hand, in Veracruz, there is also a higher diversity of other organisms, such as small- and medium-sized mammals [81] in the rustic Huatusco plantations than in the simple polycultures of Huatusco, and in the different agroforestry systems of Coatepec.…”
Section: Discussionsupporting
confidence: 93%
“…Investigation of endophytic fungi communities of Taxus chinensis var. mairei, distributed in Jiangxi, Zhejiang and Chongqing regions of China, gave similar results (Wu et al 2013b). Endophytic fungi of the same plant species in the same area are basically similar, but for some fungi, the abundance and distribution differs with the age and the tissue of plants (Arnold and Herre 2003;Mei et al 2014).…”
Section: Distribution Of Endophytic Fungimentioning
confidence: 50%
“…The ability of many endophytes to protect plants from herbivores by producing toxins, improve plant tolerance to abiotic stress or confer resistance to plant pathogens is known to all (Hyde and Soytong 2008). Some previous studies of endophytic fungi concentrated on plant leaves (Botella and Diez 2011;Koukol et al 2012;Sánchez Márquez et al 2007), roots (Keim et al 2014), or above-ground tissues of host plants (Kusari et al 2013;Wu et al 2013), and a few studies have compared the endophytic fungi between aboveground and below-ground of plant organs (Sánchez Márquez et al 2010;Su et al 2010;Vujanovic et al 2012;Jiang et al 2013;Zhang et al 2014). Although the ubiquity of endophytic fungi in plants, the ecological significance of these symbionts, including their contribution to plant fitness and adaptation, the way in which endophytes interact with the host and the mechanisms responsible for the beneficial attributes of colonization still remain unclear (García et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Strobel and Daisy (2003) indicated that areas of high biodiversity and with high numbers of endemic plant species may hold the most potential for endophytes with novel chemistry. However, only a few of the medicinal Chinese plants were studied as a source of bioactive endophytic fungal communities (Wu et al 2013). However, only a few of the medicinal Chinese plants were studied as a source of bioactive endophytic fungal communities (Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%